Proliferating cell nuclear antigen immunoreaction in adrenal-tumors - Damiani, D.; Manna, T. D.; Aquino, LGW; Alves, F.; Longatto, A.; Kanamura, C. T.; Setian, N. (Casa Editrice Ambrosiana, 1995)
Aims mid background: We studied, retrospectively, 33 cases of adrenal tumors of children at the Pediatric Endocrinology Unit, Children's Institute, Sao Paulo State University Medical School, from 1975 to 1993. Ail patients had at least 2 years of follow-up with a few exceptions. Methods: Clinical follow-up data were correlated with histopathologic review, laboratory data and cell kinetic evaluation (based on detection of proliferating cell nuclear antigens). Results: With one exception, all the patients had presented signs of androgen production and had high levels of dehydro-epiandrosterone-sulfate. Tumor weight evaluation represented a good parameter of neoplasm evolution: of 19 cases weighing less than 250 g, 17 had no evidence of disease after surgery, and 2 had an unfavorable prognosis. Of 14 cases weighing more than 250 g, only 1 had no evidence of disease and 13 had an unfavorable evolution. Conclusions: Proliferating cell nuclear antigen (PCNA) was not helpful to evaluate adrenal neoplasm evolution: our study did not show any correlation between PCNA score and prognosis.
Keywords: ADRENAL NEOPLASMS; PROLIFERATING CELL NUCLEAR ANTIGEN; CELL KINETICS; PEDIATRIC NEOPLASMS; ENDOCRINOLOGIC NEOPLASMS